New discoveries of vertebrates from a near-shore marine fauna from the Early Miocene of northwestern Venezuela - Sánchez-Villagra, Marcelo R. (2001)
New discoveries from a recently described nearshore marine fauna from northwestern Venezuela of presumed early Miocene age are reported. The fossils consist of a cranial portion of a crocodile assigned to the Tbmistominae, confirming the presence of this group in South America, and the scapula of a cetacean with affinities to the Platanistoidea. The stratigraphic section of the fossil locality ‘Cerro La Cruz’ consists of ca. 87 m of clayey marls interbedded with thin hardground units, with the upper strata being gypsiferous. The fossils were found in sandstones stratigraphically above this sequence.